2022
DOI: 10.3389/fphys.2022.1045870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional training on sprinting, jumping, and functional movement in athletes: A systematic review

Abstract: This systematic review aims to illuminate the effects of functional training on sprinting, jumping, and functional movements in athletes. A systematic search of electronic databases—that include PubMed, EBSCOhost (Sport Discus), SCOPUS, ProQuest, Google Scholar, and additional references—was carried out using keywords associated with functional training, jumping, sprinting, functional movement skills, and athletes, in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
2
2
Order By: Relevance
“…The results illustrated the significant improvement in linear sprints across 20–40 m in basketball players with FT. These results are not in line with those reported in a previous systematic review ( Bashir et al, 2022 ) examining athletes from different team sports. Bashir et al (2022) reported that the improvement in some linear speed performance among athletes after FT was not observed in a small number of studies due to the short duration and frequency of the training sessions, as well as the absence of additional exercises accompanying the FT interventions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results illustrated the significant improvement in linear sprints across 20–40 m in basketball players with FT. These results are not in line with those reported in a previous systematic review ( Bashir et al, 2022 ) examining athletes from different team sports. Bashir et al (2022) reported that the improvement in some linear speed performance among athletes after FT was not observed in a small number of studies due to the short duration and frequency of the training sessions, as well as the absence of additional exercises accompanying the FT interventions.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are not in line with those reported in a previous systematic review ( Bashir et al, 2022 ) examining athletes from different team sports. Bashir et al (2022) reported that the improvement in some linear speed performance among athletes after FT was not observed in a small number of studies due to the short duration and frequency of the training sessions, as well as the absence of additional exercises accompanying the FT interventions. However, the studies included in our review may have incorporated FT stimuli that enhanced the coordination between the nervous system and muscles, which is important for executing the complex movements involved in sprinting ( Keiner et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Fighting in combat sports often results in enormous stress on the body, and the risk of injury is very high. Functional training helps prepare an athlete's body as a whole, including strengthening core muscles, increasing joint stability, and improving body coordination (Bashir et al, 2022). Therefore, it can help reduce the risk of injury and extend the athlete's career.…”
Section: Discussionmentioning
confidence: 99%
“…Power was assessed through tests like the standing long jump (SLJ)[3,27], countermovement jump (CMJ) [9,71,100] and medicine ball throw(TMBP)[112]. Muscular endurance was evaluated by the number of 1-minute sit-ups (SU)[17,38], number of push-ups (PSU)[13,50], and number of pull-ups (PLU)[12].…”
Section: Methodsmentioning
confidence: 99%